Validation of a finite element model of the thoracolumbar spine to study instrumentation level variations in early onset scoliosis correction. (May 2021) - Roth, Alex K.; Beheshtiha, Alireza Sh.; van der Meer, Ronald; Willems, Paul C.; Arts, Jacobus J.; Ito, Keita; van Rietbergen, Bert
Abstract: Growth-guidance constructs are an alternative to growing rods for the surgical treatment of early onset scoliosis (EOS). Constructs containing ultra-high molecular weight polyethylene (UHMWPE) sublaminar tape have been proposed as an improvement to the traditional Luque trolley. Ideally, a certain minimum number of levels is instrumented, thus offering the best balance between providing adequate spinal fixation and minimizing surgical exposure and spinal mobility reduction. The objective of the current study was to validate a parametric FE model of the thoracolumbar spine including its ability to predict the biomechanical effects of varying the number of levels instrumented with UHMWPE sublaminar tape in a growth-guidance construct for EOS correction. In a first step, the material properties of the L4-L5 segment in the model were calibrated relative to literature data. Next, whole thoracolumbar spine behavior was verified relative to literature data as well. Subsequently, rods, screws, and sublaminar tape were implemented in the model and a simulation of a previously performed in vitro experiment, in which the range of motion (ROM) of porcine spine segments was measured for different tape configurations, was performed. Good agreement between in vitro and FE-results was found for the changes in ROM before and after instrumentation. Good agreement for changes in ROM was obtained when varying the number of instrumented levels as well, indicating that the model can be a useful tool to evaluate the effects of construct composition variations. The present study was limited by the fact that only normal spine curvatures were analyzed and the fact that results of porcine spine experiments were compared to results of human FE models. Nevertheless, the good agreement in results, even at a detailed level, supports the idea that the model can ultimately be used as a pre-operative planning tool to evaluate different construct designs. The FE model of the thoracolumbar spine was successfully validated and was able to capture the biomechanical effect of construct component variations. Graphical abstract: Image 1 Highlights: UHMWPE sublaminar tape fixation may offer benefit for early onset scoliosis patients. FE modeling may support pre-operative design of spinal instrumentation composition. Material properties are calibrated and behavior of the motion segment is validated. Construct variation is validated relative to an in vitro biomechanical experiment.